SENIOR HIGH SCHOOL TEACHERS STRATEGY IN ONLINE LEARNING - Dela Astria Budiarti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This study concerns about the application used by English teacher, strategy used by English teacher and students’ accomplishment in online learning in term of senior high school. Two English teachers of MA Bilingual Batu were chosen as subjects of this study. This study aims to investigate those three condiments. The data was collected by researcher in term of transcript document. The researcher did interview to gain the data. The findings for this study obtained that WhatsApp and Google Classroom as the most application used by English teachers at MA Bilingual Batu. Meanwhile the strategies used by English teacher at MA Bilingual Batu are set induction strategy, stimulus variation strategy and use effective question strategy. The students’ accomplishment indicated that in the daily assignment the score of students were good but in the midterm test were low. It can be said that the implementation of online learning must be considered again especially for the election of application used, strategy used by teachers and students’ accomplishment.Keywords: application, strategy, students’ accomplishment, online learning.